HORECA MARKETPLACE: AN INNOVATIVE PLATFORM FOR SMALL AND MEDIUM-SIZED BUSINESSES - Obolentseva, L.; Sokolenko, А.; Davydov, Y. (Municipal economy of cities. Series: «Economy science», 2022)
The article is devoted to the development of a conceptual business model of a marketplace focused on the restaurant business. Search for suppliers and potential consumers, along with the availability of information, remains one of the main issues of the market. Thus, the development of a marketplace model for HoReCa can be a solution to the search issues of both sides of business. Marketplaces are considered as a result of digitalization of economic society. Marketplaces act as an intermediary between the consumer and the seller, performs the functions of a market operator that processes consumer transactions and transmits information about orders to sellers. For certain marketplaces, the phenomenon of free or flexible pricing can be characteristic, when the prices of goods and services are determined directly by the interaction of suppliers and consumers. The article focuses on information availability and customer orientation of marketplaces. Marketplaces combine products and services from a wide range of suppliers, which is a key difference from an online store. It is worth noting that modern services provide a range of interaction models: business-to-business (B2B), business-to-consumer (B2C), business-to-government (B2G), consumer-to-consumer (C2C) and others. Considering specifics of the market, the article proposes to apply a combined model of interaction: B2B with features of C2C. Using such a model will provide an opportunity to placing orders and offers both to suppliers and HoReCa representatives. The article analyzes the key legal issues of opening such an innovative platform. Due to existing financial restrictions, marketplaces do not participate in the payment processing of orders, as the activity of a payment intermediary is considered a financial service and can only be performed by a financial institution. Despite these limitations, the conceptual model of the marketplace proposed in the article offers solutions to most of the current problems and challenges.